2022
DOI: 10.1038/s41598-022-24406-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of lysophosphatidylcholine 14:0 as a biomarker for drug-induced lung disease

Abstract: Drug-induced interstitial lung disease (DILD) occurs when drug exposure causes inflammation of the lung interstitium. DILD can be caused by different types of drugs, and some DILD patterns results in a high mortality rate; hence, DILD poses a serious problem in clinical practice as well as drug development, and strategies to diagnose and distinguish DILD from other lung diseases are necessary. We aimed to identify novel biomarkers for DILD by performing lipidomics analysis on plasma samples from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Similar to the biomarkers identified in this study, we have reported that plasma LPC(14:0) levels can be used as a biomarker for discriminating DILD from IIPs and CTD [ 19 ]. However, the drawbacks of LPC(14:0) in the differential diagnosis of DILD include that its plasma concentration also changes in patients with BP.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to the biomarkers identified in this study, we have reported that plasma LPC(14:0) levels can be used as a biomarker for discriminating DILD from IIPs and CTD [ 19 ]. However, the drawbacks of LPC(14:0) in the differential diagnosis of DILD include that its plasma concentration also changes in patients with BP.…”
Section: Discussionsupporting
confidence: 70%
“…The metabolomic profile also provides a comprehensive readout of individual responses to treatment, which may enhance the discovery of biomarkers for the efficacy and adverse effects of drugs [ 18 ]. Indeed, several new biomarkers (lysophosphatidylcholines [LPCs]) for DILD were identified in our previous metabolomic study focusing on lipids [ 19 ], which showed that LPCs distinguish DILD from IIPs and CTD, but decreased plasma concentrations of LPCs can be observed not only in patients with acute DILD but also those with bacterial pneumonia (BP) [ 19 ]. Thus, a novel biomarker specific to DILD needs to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…One more example is inflammation induced by drug exposure, which has an effect on LPC concentrations. In a recent study, LPCs were reported as potential biomarkers for drug-induced interstitial lung disease [ 84 ]. The selected biomarkers showed no associations with other drugs and were effectively implemented to differentiate between other lung diseases: idiopathic interstitial pneumonia and lung disease associated with connective tissue disease.…”
Section: Research Field Landscapementioning
confidence: 99%
“…14,15 Notably, lipids are considered appropriate targets for biomarker development. 16 Consequently, there is a rising interest in employing lipidomics to discover appropriate biomarkers for clinical application, identify novel targets for therapeutic intervention in disease progression, and unravel the underlying molecular mechanisms involved. 17 Due to practical and ethical concerns, very limited experiments can be conducted on human subjects; animal models spanning from non-mammalian models to non-human primates (NHPs) remain indispensable for the pharmacological testing and elucidation of the mechanism of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS)‐based lipidomics can be conducted through untargeted and targeted fashion, each with their own distinct features, and a combination of these two approaches is often utilized to maximize the coverage of lipid species detected and quantified in complex biological samples 14,15 . Notably, lipids are considered appropriate targets for biomarker development 16 . Consequently, there is a rising interest in employing lipidomics to discover appropriate biomarkers for clinical application, identify novel targets for therapeutic intervention in disease progression, and unravel the underlying molecular mechanisms involved 17 …”
Section: Introductionmentioning
confidence: 99%